Protection and salvation: an eleventh-century silver vessel, its imagery, and its function - Frentrop, Lara (Byzantine and modern Greek studies, 2018)
A small silver bowl, discovered in Russia and usually attributed to eleventh-century Byzantium, displays a range of unusual imagery that has complicated its interpretation. The role of the saint and prayer on the vessel and the emphasis placed on intercession as well as on protection, this paper will suggest, was to protect the vessel's owner both on earth and in his afterlife. The vessel, which makes visible contemporary ideas about punishment, Last Things, and salvation, presents a fragmentary image of the Last Judgement designed to stress the importance of heavenly justice and to remind its viewer to remain virtuous.